Evaluasi Tingkat Pengetahuan Mahasiswa Pendidikan Profesi Apoteker UNTAN melalui Kegiatan Matrikulasi - Kurniawan, Hadi; Untari, Eka Kartika (Jurnal Pendidikan Kesehatan (e-Journal), 2022)
Matriculation is a series of activities to welcome new students and institutional service for new students whereas they are accepted not only from alumni of Tanjungpura University with diverse backgrounds, especially academic and social abilities. This activity is needed to uniform and to harmonize academic skills and support students readiness in Pharmacist Professional Education Study Program at University of Tanjungpura, so the students are expected to pass the educational process and to pass the competency test. In addition, to refresh and to increase the knowledge and understanding of new students when they attend lectures, providing to new students already have a basic concept of knowledge that will be studied in pharmacist professional education. The method used was one group pretest-posttest design. The results of the activity showed that matriculation can increase and affect the value of student learning outcomes significantly with the pretest average score indicator at 46.35933 (scale 0 until 100) to 65.89633 (scale 0 until 100) of post-test average score. The results of filling out the questionnaire indicated that this activity was considered very useful and hoped that the activity would be continuing.